POLIGAMI - Abdur Rohman (State Institute of Islamic Studies Batusangkar, 2019)
One controversial issue in Islam is polygamy. This paper describes polygamy from: before Islam, during the Islamic period of the Prophet and Companions, the concept of fair, dowry, marriage controversy with ‘Aishah and the world's population. This paper concludes polygamy in Islam is the limitation of unlimited polygamy marriage practice of Arabian people. Polygamy during the time of the Prophet was assumed as God's commands rather than lust and the polygamy practices of Prophet Companions tended as a great people aspect rather than forcing women to be their wives. Then, the concept of fair in polygamy can be measured by wives; the Prophet's dowry to his wives was very huge, and the world population provided the opportunity to conduct polygamy.